A Review on the HPLC Method Development and Validation Studies of Combined Dosage Form of Rosuvastatin and Ezetimibe - Chandran, Sajith Kumar Chandran (Asian Journal of Pharmaceutical Research and Development, 2024)
Analytical method development is an important aspect of drug development and manufacturing. An exceptional analytical method is the one which detects the active pharmaceutical ingredients as well as the impurities and other chemical entities which invariably enters the formulations due to various reasons. The methods which are developed accordingly are to be validated as per the ICH guidelines so as to be accepted in a commercial setting. Coronary Artery Disease is a life threatening condition, which affects millions of people, where the blood flow to the heart is affected due to plaque deposits. Patients are administered with combined dosages of Rosuvastatin and Ezetimibe for the effective treatment and management of the disease. Various pharmaceutical formulations are available with the combined dosage forms and analytical method development is necessary during the development of the drug so as to detect impurities and ascertain safety and efficacy. HPLC is the most effective and reliable methodology for the analysis of the pharmaceutical drug dosages which are released to the market by pharmaceutical companies. The review focus on the various methodologies developed over the years to effectively analyse the combined drug formulations of Rosuvastatin and Ezetimibe as per the ICH guidelines.